2014
DOI: 10.1007/s11136-014-0683-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anxiety sensitivity, pain hypervigilance, and pain catastrophizing on quality of life outcomes of patients with chronic pain: a preliminary, cross-sectional analysis

Abstract: These cross-sectional analyses gave results consistent with pain hypervigilance, mediating the relationship of pain catastrophic cognition and anxiety sensitivity with pain-related fear. The net suppression effects of pain catastrophizing point to anxiety sensitivity, enhancing the effect of pain catastrophic cognition on pain hypervigilance. These findings elucidate how the interdependence of dispositional factors might influence pain adjustment and functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
3
34
0
2
Order By: Relevance
“…La activación del SIC haría que la atención se redirigiera a las señales relacionadas con el dolor (que se asemejan a un "castigo"), con el propósito de anticiparlo y evitarlo lo que, sin embargo, provoca un aumento del nivel percibido del mismo (1,39,40). Esta percepción conllevaría la activación negativa del SAC (puesto que este sistema se activa ante señales de refuerzo y recompensa, no de castigo) y/o su hipoactivación (no desactivación total), debido a la existencia de una influencia bidireccional entre ambos sistemas (41).…”
Section: La Teoría De La Sensibilidad Al Reforzamiento Como Marco Expunclassified
“…La activación del SIC haría que la atención se redirigiera a las señales relacionadas con el dolor (que se asemejan a un "castigo"), con el propósito de anticiparlo y evitarlo lo que, sin embargo, provoca un aumento del nivel percibido del mismo (1,39,40). Esta percepción conllevaría la activación negativa del SAC (puesto que este sistema se activa ante señales de refuerzo y recompensa, no de castigo) y/o su hipoactivación (no desactivación total), debido a la existencia de una influencia bidireccional entre ambos sistemas (41).…”
Section: La Teoría De La Sensibilidad Al Reforzamiento Como Marco Expunclassified
“…Indeed, chronic pain patients have reported greater levels of anhedonia and decreased responsiveness to rewards, relative to healthy controls (Elvemo, Landrø, Borchgrevink, & Håberg, 2015), and distress tolerance has been implicated in emotion regulation and coping among persons with chronic pain (Hamilton, Karoly, & Kitzman, 2004). Moreover, decades of research have consistently demonstrated that greater levels of anxiety sensitivity predict a range of negative pain-related outcomes, including greater use of analgesic medications, greater cognitive bias toward pain experiences, and greater activation of fear-avoidance mechanisms (e.g., pain-related fear) that contribute to the development and maintenance of pain-related disability (e.g., Asmundson & Norton, 1995; Keogh & Cochrane, 2002; Wong et al, 2014). Thus, we suggest that transdiagnostic factors relevant to anxiety/depression should also be considered when addressing complex interrelations among affect, pain, and tobacco smoking.…”
Section: Anxiety and Depression In Bidirectional Pain–smoking Relationsmentioning
confidence: 99%
“…It is well known that the way a person is attending to pain can have a direct effect not only on the experience of pain at that given moment but might also contribute to the development of chronic pain [13]. Moreover, pain patients who are highly attentive to pain have been found to engage in fewer productive activities and report greater levels of distress, disability, anxiety, and depression [1].…”
Section: Introductionmentioning
confidence: 99%